Fashion and art under the sight of psychoanalisys (ModaPalavra e-periódico, 2008)
Fashion and art, in early times are present in all communication fields, materializing desires and needs. However it´s extremely deep the action of creating, observing and consuming, once this acts are so close to psychologic of human being. Many social sciences, like philosophy and sociology, discuss the intensity of these movements of expression, but psychoanalisys will give theory for the investigation of uncounscious at the humans identity and yours daily conceptions. In this assay of research, the intention is in demonstrating how intense the theories of Jacques Lacan are in the daily of human beings, through the messages emmited by arts in general and fashion, assisting the construction of this semiotic being extremely complex, but infinitely interesting.
Keywords: Psychoanalysis; Arts; Fashion